The CRITICAL SUCCESS FACTORS FOR SUSTAINABLE ENTREPRENEURSHIP IN CAMBODIA - Sithambalam, Yamuna; Abu Talib, Alyaa Afifah; ELANGO, DINESH; Talib, Zunirah Mohd (Journal of Research and Multidisciplinary, 2024)
This paper aims to examine relevant literatures to identify critical success factors for sustainable entrepreneurship in Cambodia and further develop a conceptual framework for future methodological research. This study begins with the review of literatures that outlined success factors for sustainable development before examining the critical success factors for sustainable entrepreneurship. A crucial finding from literature shows that there is inconsistency between the success factors for sustainable development and sustainable entrepreneurship despite some literatures identifying sustainable entrepreneurship as a business model being built based on the United Nation’s Sustainable Development Goals (SDG). The main sources of inconsistencies are the various stages of economic development and government policies across the countries being researched. Gaudemar (2016) mentioned despite having made progress in advancing development, Cambodia is unlikely to ‘graduate’ from its Least Developed Country (LDC) status till 2025 and beyond. There is probability that the framework will be a valuable tool for meticulous analysis and evaluation of critical success factors for sustainable entrepreneurship in Cambodia. The limitation of this study is that the model is purely conceptual and requires further validation with in-depth methodological research.